Molecular mechanisms associated with oxidative damage in the mouse testis induced by LaCl3. Issue 3 (24th October 2020) - Ji, Jianhui; Hong, Fashui; Zhou, Yingjun; Liu, Tingwu; Fan, Dongxue; Zhang, Xingxiang; Lu, Yutian; Jiang, Lingling; Wang, Xiaomei; Wang, Chen
Abstract: China is the world's largest rare earth producer and exporter, previous studies have shown that rare earth elements can cause oxidative damage in animal testis. However, the molecular mechanisms underlying these observations have yet to be elucidated. In this paper, male mice were fed with different doses (10, 20, and 40 mg/kg BW) of LaCl3 for 90 consecutive days, regulatory role of nuclear factor erythroid‐2 related factor 2 (Nrf‐2)/antioxidant response element (ARE) pathway in testicular oxidative stress induced by LaCl3 were investigated. Analysis showed that LaCl3 exposure could lead to severe testicular pathological changes and apoptosis in spermatogenic cells, it up‐regulated the peroxidation of lipids, proteins and DNA, and induced the excessive levels of reactive oxygen species (ROS) production in mouse testis, reduced the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), and glutathione S epoxide transferase (GST) as well as the glutathione (GSH) content. Furthermore, exposure to LaCl3 also downregulated the expression of Nrf2 and its target gene products, including heme oxygenase 1 (HO‐1), glutamate‐cysteine ligase catalytic subunit (GCLC), NAD(P)H dehydrogenase [quinine] 1(NQO1), protein kinase C (PKC), and phosphatidylinositol 3‐kinase (PI3K), but upregulated the expression of Kelch‐like ECH‐related protein 1 (Keap1) in damaged mouse testes. Collectively, our data imply that the oxidative damage induced by LaCl3 in testis was related to inhibition of the Nrf‐2/AREs pathway activation.